Stability of ionic liquid modeled by composite Coulomb-Yukawa potentials - Bossa, Guilherme Volpe [UNESP]; May, Sylvio (Amer Physical Soc, 2020)
An ionic liquid modeled as a densely packed lattice with composite ion-specific Coulomb-Yukawa pair interactions tends to be unstable near a planar electrode, given the Yukawa potential mediates an effective short-range attraction of the ions. We present a comprehensive mean-field model, accounting for ion-specific electrode-ion interactions and for the propagation of the Yukawa field into the electrode. The surface instability precedes the spinodal instability of the ionic liquid and may thus lead to hysteresis and to a large differential capacitance in the metastable region of the phase diagram, but not necessarily to oscillations of the net charge density.